COVID19 and the Media Introductory Note. (August 2020) - Russell, Adrienne; Powers, Matt
All of the authors who have contributed to this issue on COVID19 and the Media have stepped out of the rush of change, if only for a 2000-word moment, to look into a corner of the mediated pandemic and grapple with the significance of what's happening in our field, our societies, our lives. We appreciate their insights, and hope you do too.